Functional mapping of protein kinase A reveals its importance in adult Schistosoma mansoni motor activity. - Paulu S R de Saram (Public Library of Science (PLoS), 2013)
Cyclic AMP (cAMP)-dependent protein kinase/protein kinase A (PKA) is the major transducer of cAMP signalling in eukaryotic cells. Here, using laser scanning confocal microscopy and 'smart' anti-phospho PKA antibodies that exclusively detect activated PKA, we provide a detailed in situ analysis of PKA signalling in intact adult Schistosoma mansoni, a causative agent of debilitating human intestinal schistosomiasis. In both adult male and female worms, activated PKA was consistently found associated with the tegument, oral and ventral suckers, oesophagus and somatic musculature. In addition, the seminal vesicle and gynaecophoric canal muscles of the male displayed activated PKA whereas in female worms activated PKA localized to the ootype wall, the ovary, and the uterus particularly around eggs during expulsion. Exposure of live worms to the PKA activator forskolin (50 µM) resulted in striking PKA activation in the central and peripheral nervous system including at nerve endings at/near the tegument surface. Such neuronal PKA activation was also observed without forskolin treatment, but only in a single batch of worms. In addition, PKA activation within the central and peripheral nervous systems visibly increased within 15 min of worm-pair separation when compared to that observed in closely coupled worm pairs. Finally, exposure of adult worms to forskolin induced hyperkinesias in a time and dose dependent manner with 100 µM forskolin significantly increasing the frequency of gross worm movements to 5.3 times that of control worms (P≤0.001). Collectively these data are consistent with PKA playing a central part in motor activity and neuronal communication, and possibly interplay between these two systems in S. mansoni. This study, the first to localize a protein kinase when exclusively in an activated state in adult S. mansoni, provides valuable insight into the intricacies of functional protein kinase signalling in the context of whole schistosome physiology.